Haiti : 2010 Article IV Consultation and Request for a Three-Year Arrangement Under the Extended Credit Facility; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Haiti. (IMF Staff Country Reports; Country Report ;, 2010)
The January 2010 earthquake represented a major setback for Haiti, after several years of improved economic performance. Executive Directors commended the authorities for quickly restoring basic government functions and maintaining sound policies during the crisis. Directors welcomed the National Action Plan for Recovery and Development and also the Partial Credit Guarantee scheme. They also stressed the need to strengthen revenue administration, monetary framework, and tax policy reforms. Directors agreed that Haiti met the eligibility and qualification criteria for debt stock relief under the Post-Catastrophe Debt Relief (PCDR) Trust Fund.